2023
DOI: 10.21203/rs.3.rs-3592034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cohort Study of Individuals with Neurodevelopmental Disorders and/or Congenital Anomalies Investigated by High- Resolution Chromosomal Microarrays in Southern Brazil: The Significance of Autism Spectrum Disorder

Tiago Fernando Chaves,
Maristela Ocampos,
Ingrid Tremel Barbato
et al.

Abstract: Chromosomal microarray (CMA) is the reference in evaluation of copy number variations (CNVs) in individuals with neurodevelopmental disorders (NDDs), such as intellectual disability (ID) and/or autism spectrum disorder (ASD), which affect around 3–4% of the world’s population. Modern platforms for CMA, also include probes for single nucleotide polymorphisms (SNPs) that detect homozygous regions in the genome, such as long contiguous stretches of homozygosity (LCSH). These regions result from complete or segmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…A large study of individuals with NDDs identified dysmorphic features in approximately 47% of cases. 23) Various syndromes with distinct dysmorphic features can also result in GDD/ID; thus, clinicians must be knowledgeable and acquainted with these conditions. Fragile X syndrome, among the most prevalent of these syndromes, is characterized by identifiable clinical features that are easily noted in affected males with the full mutation.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…A large study of individuals with NDDs identified dysmorphic features in approximately 47% of cases. 23) Various syndromes with distinct dysmorphic features can also result in GDD/ID; thus, clinicians must be knowledgeable and acquainted with these conditions. Fragile X syndrome, among the most prevalent of these syndromes, is characterized by identifiable clinical features that are easily noted in affected males with the full mutation.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Additionally, gait apraxia, kyphoscoliosis, sleep disturbances, episodes of laughter and cream, and a reduced response to pain are other variable characteristics of this disorder. 2,12,23,24) Anomalies affecting the musculoskeletal system, eyes, heart, genitourinary tract, and connective tissues may also be discerned during routine systemic physical examinations, potentially those indicating a specific diagnosis or guiding laboratory investigations. Behavioral assessment provides the basis for describing any atypical pattern of a child's behavior, such as aggression, repetitive and selfinjurious behavior, decreased social engagement, and impulsivity.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%